The Synthesis of Metalcarbon Nanocomposite Ni / C on the Basis of Polyacrylonitrile - L.V. Kozhitov; D.G. Muratov; E.V. Yakushko; S.L. Kozhitov; A.G. Savchenko; I.V. Shchetinin; S.G. Emelyanov; L.M. Chervjakov (Журнал нано- та електронної фізики)
Metalcarbon nanocomposites based on polyacrylonitrile and nickel chloride are synthesized under the influence of infrared heat. The resulting materials represent a system of carbon matrix formed during the carbonization of PAN, and distributed in it nickel nanoparticles. The average size of the nanoparticles in the nanocomposite was 15-25 nm. It was found that the distribution of nickel nanoparticles sizes is determined by temperature synthesis nanocomposite. Thus with increasing temperature, the predominant average particle size of the metal increases, and the distribution is spread and shifted toward larger sizes.